PENANAMAN NILAI AGAMA DAN MORAL YANG BERBEDA PADA ANAK USIA DINI DI TK DHARMA WANITA LIMA PULUH KABUPATEN BATU BARA - Yusnani Batu Bara; Neni Afriani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2021)
Instillation of religious and moral values is a very important part that can shape the character of children from children's self-development that has been formulated in the development of aspects of child development. The process of instilling religious and moral values in children begins early, because this period tends to be more effective and easier to get used to in children so that it becomes a good habit in the future. The strategies of teachers in Dharma Wanita Kindergarten in nurturing religious and moral values are carried out through routine activities that are carried out every day starting from the child coming until the child is picked up by his parents, which includes: Activities to say greetings, pray before studying, pray before and after meals, activities to play together with mutual respect for others, inculcate honesty, love each other, and instill tolerance so as not to distinguish between friends.activities of reading short surahs and daily prayers and prayers, iqro reading activities and learning to know the creator with friends.